Disinhibition in children with attention-deficit/hyperactivity disorder: Changes in oxy-Hb on near-infrared spectroscopy during "rock, paper, scissors" task - Ishii, Sayaka; Kaga, Yoshimi; Tando, Tomoko; Aoyagi, Kakuro; Sano, Fumikazu; Kanemura, Hideaki; Sugita, Kanji; Aihara, Masao (Brain & development (Tokyo. 1979), 2017)
Attention-deficit/hyperactivity disorder (AD/HD) is a common developmental disorder. Many reports have suggested that symptoms of AD/HD are related to frontal lobe dysfunctions, particularly disinhibition. However, measuring neurological findings with biomarkers during frontal functional tasks has sometimes been difficult in children with AD/HD. This study aimed to investigate frontal inhibitory function objectively in children with AD/HD during "rock, paper, scissors" (RPS) tasks, as a familiar game for Japanese children, using near-infrared spectroscopy (NIRS).OBJECTIVEAttention-deficit/hyperactivity disorder (AD/HD) is a common developmental disorder. Many reports have suggested that symptoms of AD/HD are related to frontal lobe dysfunctions, particularly disinhibition. However, measuring neurological findings with biomarkers during frontal functional tasks has sometimes been difficult in children with AD/HD. This study aimed to investigate frontal inhibitory function objectively in children with AD/HD during "rock, paper, scissors" (RPS) tasks, as a familiar game for Japanese children, using near-infrared spectroscopy (NIRS).Eighteen children with AD/HD were compared with 27 typically developing children (TDC). Children from each group were divided into two age groups: younger, 6-10years; and older, 11-16years. Changes in oxygenated hemoglobin [oxy-Hb] were measured in the prefrontal region using NIRS during a 'to lose' RPS task, in which subjects were asked to present the RPS signal that would lose in response to one of the three signals displayed randomly on a computer screen every 2.0s.SUBJECTS AND METHODSEighteen children with AD/HD were compared with 27 typically developing children (TDC). Children from each group were divided into two age groups: younger, 6-10years; and older, 11-16years. Changes in oxygenated hemoglobin [oxy-Hb] were measured in the prefrontal region using NIRS during a 'to lose' RPS task, in which subjects were asked to present the RPS signal that would lose in response to one of the three signals displayed randomly on a computer screen every 2.0s.The rate of correct performance with both TDC and AD/HD increased with age. Only in the older group, the rate of correct performance was significantly higher with TDC than with AD/HD. However, children with AD/HD in both age groups showed significantly lower [oxy-Hb] activity in the prefrontal region during the 'to lose' RPS task, particularly in the dorsolateral area.RESULTSThe rate of correct performance with both TDC and AD/HD increased with age. Only in the older group, the rate of correct performance was significantly higher with TDC than with AD/HD. However, children with AD/HD in both age groups showed significantly lower [oxy-Hb] activity in the prefrontal region during the 'to lose' RPS task, particularly in the dorsolateral area.Our results suggest that prefrontal region activation during the 'to lose' RPS task could offer a biomarker for diagnosing AD/HD, and may help in the early treatment of AD/HD.CONCLUSIONSOur results suggest that prefrontal region activation during the 'to lose' RPS task could offer a biomarker for diagnosing AD/HD, and may help in the early treatment of AD/HD.